ZnO based triboelectric nanogenerator on textile platform for wearable sweat sensing application. (April 2023) - Baro, Bikash; Khimhun, Sammun; Das, Upamanyu; Bayan, Sayan
Abstract: Here we report the fabrication of textile based wearable sweat sensor working under the principle of triboelectrification. Single electrode triboelectric nanogenerator (STENG) composed of chemically grown zinc oxide (ZnO) nanorods on textile platform has been explored for sweat sensing application. It has been found that the STENG can be operated through biomechanical movements to work as motion sensor. Again, the incremental nature of the output of the STENG under the variation in saline water concentration, signifies the applicability of the same as sweat sensor. It has been proposed that the attachment of hydrated Cl ions of saline water upon attachment with the physisorbed water molecule of ZnO, increases the conduction band electron in ZnO. Consequently, the amount of charge transfer between ZnO and counter triboelectric layer increases and thus yields higher output voltage. To find the efficacy of the system for practical sweat sensing application, miniaturized proof of concept prototype of the STENG (∼ 1 cm diameter) has been developed and is found to be efficient in sweating condition upon attaching to human body. The fabricated prototype is found to exhibit a sensitivity of ∼ 0.02 V/µL, along with a detection limit of ∼ 4.8 µL. Further, upon attaching the prototypes of motion sensor and sweat sensor to a shoe insole, the detection of sweat under foot movement has been demonstrated. Finally, the remote sensing of the signals generated by the textile based STENG has been demonstrated upon integrating it to a microcontroller unit and transmitting the output wirelessly to an electronic gadget. Graphical Abstract: ga1 Highlights: Fabrication of zinc oxide (ZnO) nanorod based single electrode triboelectric nanogenerator (STENG) on textile platform. Exhibition of STENG operation through biomechanical movements for application in motion sensor. Demonstration of sweat sensing characteristics of ZnO STENG and exploration of the sensing mechanism. Development of proof of concept prototype sweat sensor with sensitivity of ∼ 0.02 V/µL and detection limit of ∼ 4.8 µL.